REVIEW OF ISLAMIC LAW AND LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION AGAINST BUYING AND SELLING STYROFOAM FOOD PACKAGING - Dara Ainal M (JURISTA: Jurnal Hukum dan Keadilan, 2021)
An ideal sale and purchase is a sale and purchase that fulfils the conditions, pillars, and other things related to buying and selling. In buying and selling food using styrofoam packaging, it is known that styrofoam used to wrap food contains za-substances that are harmful to health. The purpose of this study is to determine the factors that cause food sellers in Syiah Kuala District to use Styrofoam as food packaging, the positive and negative impacts of using Styrofoam on food packaging in the economic and health aspects, as well as the review of Islamic law and GCPL Law on the sale and purchase of Styrofoam food packaging. The method used in this research is descriptive analysis which later researchers will conduct research through the field or literature, as for data collection techniques, namely through observation and interviews. The results of this study are the factors that cause food traders in Syiah Kuala District to use Styrofoam as food packaging are in terms of price, cleanliness, prevalence, and convenience. The positive impact of using Styrofoam on food packaging in the economic aspect because of its low price while the negative impact from the health aspect is that it can endanger consumer health and cause various diseases. In terms of Islamic law, the sale and purchase contract of styrofoam packaged food is fasid because it does not fulfil one of the conditions of the object of sale and purchase, which must be able to be used properly and in accordance with the provisions of Islamic law, namely not causing mudharat or something that harms and harms humans. Food can be contaminated by harmful substances contained in Styrofoam and cause harm to the buyer in the form of endangering the buyer's health and causing illness, so that there is no benefit in the sale and purchase transaction. The sale and purchase transaction violates GCPL article 4 letter a and article 8 paragraph (1).